Modified Function Projective Synchronization between Different Dimension Fractional-Order Chaotic Systems - Ping Zhou; Rui Ding (Abstract and Applied Analysis)
A modified function projective synchronization (MFPS) scheme for different dimension fractional-order chaotic systems is presented via fractional order derivative. The synchronization scheme, based on stability theory of nonlinear fractional-order systems, is theoretically rigorous. The numerical simulations demonstrate the validity and feasibility of the proposed method.